2008
DOI: 10.5858/2008-132-265-catamo
|View full text |Cite
|
Sign up to set email alerts
|

Composite Adenomatoid Tumor and Myelolipoma of Adrenal Gland: Report of 2 Cases

Abstract: Adenomatoid tumor and myelolipoma are benign, hormonally inactive tumors that are often incidental findings in the adrenal glands. Myelolipoma is more common than adenomatoid tumor in this location but both are rare, and as yet, the pathogenesis of both remains unclear. We report 2 cases of composite adenomatoid tumor and myelolipoma, incidentally found in the adrenal gland on investigation for other diseases. To our knowledge, composite adenomatoid tumor and myelolipoma of adrenal gland has not been previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Adenomatoid tumor (AT) of the adrenal gland is extremely rare. From 1988 to 2020, only 39 cases of adrenal AT were reported in the English medical literature, among which only four authors reported more than one case of adrenal AT (6,10,14,18), and the rest was a single case report. Here we report two novel cases and review the literature to summarize the clinical, morphological, immunohistochemical, and prognostic features of adrenal AT more comprehensively than before.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Adenomatoid tumor (AT) of the adrenal gland is extremely rare. From 1988 to 2020, only 39 cases of adrenal AT were reported in the English medical literature, among which only four authors reported more than one case of adrenal AT (6,10,14,18), and the rest was a single case report. Here we report two novel cases and review the literature to summarize the clinical, morphological, immunohistochemical, and prognostic features of adrenal AT more comprehensively than before.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two cases of adrenal AT in a man who sought evaluation of renal colic or acute right flank pain due to nephrolithiasis were reported by Denicol et al (13) and Varkarakis et al (15), respectively. A few patients had a history of sarcoma (6), inguinal hernia (18), colon cancer (20), and mucoepidermoid carcinoma (11), and adrenal AT was incidentally discovered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations